Practical and Multidisciplinary Review on Wilson Disease: The Portuguese Perspective - Filipe Calinas; Hélder Cardoso; Sofia Carvalhana; José Ferreira; Cristina Gonçalves; Marina Magalhães; Helena Pessegueiro Miranda; José Presa; Carla Rolanda; Arsénio Santos; Rui M. Santos (GE: Portuguese Journal of Gastroenterology)
Wilson disease (WD) is a genetic disorder of copper metabolism caused by mutations in the ATP7B gene resulting in toxic copper accumulation in several organs. WD can manifest as liver disease, a progressive neurological disorder, a psychiatric illness, or a combination of these. Other clinical manifestations can also occur. Diagnosis is challenging and typically requires a range of biochemical tests, imaging, genetic testing for ATP7B, and/or liver biopsy. WD is treatable with chelating agents, such as d-penicillamine and trientine, and/or zinc salts alongside with dietary copper restriction. Liver transplantation may be indicated in WD patients with severe hepatic disease, and cautiously considered in patients with neurological WD. Treatment success highly depends on patient adherence and treatment persistence. Therefore, effective interventions for improving patient adherence and close monitoring are key for preventing WD progression. In Portugal, there are no reference centers for WD, and patients are dispersed across numerous medical specialists. This review aimed to summarize the most recent and relevant information for the diagnosis, treatment, and monitoring of WD in Portugal, as well as possible interventions for stimulating adherence to treatment.